P460 Biomarkers reflecting extracellular matrix turnover and inflammation can be used to monitor disease activity and treatment response in patients with Crohn's disease undergoing infliximab induction therapy. (27th May 2021) - Sorokina Alexdóttir, M; Bourgonje, A R; Asser Karsdal, M; Bay-Jensen, A C; Faber, K N; Loveikyte, R; van Dullemen, H M; Visschedijk, M C; Festen, E A M; Weersma, R K; Dijkstra, G; Mortensen, J H
Abstract: Background: Crohn's disease (CD) is a relapsing-remitting inflammatory disease of the gastrointestinal (GI) tract characterized by high protease activity and increased extracellular matrix (ECM) turnover. Although immunotherapeutic drugs such as anti-TNFα have shown great promise in the treatment of CD, still up to 20–40% of patients do not respond to therapy. Failure to establish effective treatment may lead to further disease progression and potential disease complications. The aim of this study was to investigate whether biomarkers of ECM turnover and intestinal inflammation could serve as non-invasive tools for monitoring treatment response to anti-TNFα in patients with CD. Methods: Serum biomarkers of matrix metalloproteinase (MMP)-related type I collagen degradation (reC1M), intestinal inflammation (VICM [macrophage activity], CPa9-HNE [serum calprotectin, neutrophil activity]) and type III collagen formation (PRO-C3) were measured using competitive ELISA in patients with CD (n=54) undergoing infliximab (IFX) induction therapy. Disease activity was defined by composite assessment of the Harvey-Bradshaw Index (HBI) together with physician's global assessments (PGA). Clinical remission (HBI <5) was assessed at week 14. Wilcoxon signed-rank tests were applied for pairwise comparisons of biomarker levels between baseline and week 14. Table 1. Differences in biomarker levels between baseline and week 14 in CD patients receiving IFX treatment stratified by response. Biomarker concentrations presented as median [IQR]. Results: In patients responding to IFX treatment ( n =50), serum levels of reC1M, VICM, and CPa9-HNE (all P <0.05) were significantly lower at week 14 compared to baseline. However, serum levels of PRO-C3 ( P <0.01) were significantly elevated in responders at week 14 compared to baseline. No significant changes were observed in the biomarkers between baseline and week 14 in those not responding to IFX treatment ( n =4). Conclusion: Serum biomarkers for type I collagen degradation (reC1M), intestinal inflammation (VICM, CPa9-HNE) and type III collagen formation (PRO-C3) are linked to the pathology of CD, reflecting treatment response. Together, these biomarkers could be used as surrogate markers for disease monitoring during IFX treatment in CD to further improve disease management.